integral curve of dx/y^2+yz+x^2= dy/y^2-xz+x^2=dz/z(x+y)
We first subtract the first expression from the second and equate to the third expression
"\\frac{dy-dx}{y^{2}+yz+x^{2}-y^{2}+xz-x^{2}}=\\frac{dz}{z(x+y)}"
"\\frac{dx-dy}{z(y+x)}=\\frac{dz}{z(x+y)}"
Simplify to get
d(x-y)=1dz
Integrate both sides
"\\int d(x-y)=\\int 1dz"
x-y+C=z
z=x-y+C1 ,this is the first integral curve
Second we add the third expression to the second and then equate with the first expression
"\\frac{dx}{y^{2}+yz+x^{2}}=\\frac{dy+dz}{y^{2}-xz+x^{2}+xz+yz}"
Simplify to get
"\\frac{dx}{y^{2}+yz+x^{2}}=\\frac{dy+dz}{y^{2}+yz+x^{2}}"
Further simply by multiplying both sides with y2+yz+x2 to get
dx=dy+dz=d(y+z)
Integrate both sides
"\\int dx=\\int d(y+z)"
x+C2=y+z
z=x-y+C2
Thus the equation only has one integral curve: z=x-y+C
Which can also be written, z-x+y=C
Comments
Leave a comment